For love or reward? Characterising preferences for giving to parents in an experimental setting - Porter, M (University of Oxford, 2014)
This paper examines the motivation for intergenerational transfers between adult children and their parents, and the nature of preferences for such giving behaviour, in an experimental setting. Participants in our experiment play a series of dictator games with parents and strangers, in which we vary endowments and prices for giving to each recipient. We find that preferences for giving are typically rational. When parents are recipients as opposed to strangers, participants display greater sensitivity to the price of giving, and a higher relative proclivity for giving. Our findings also provide evidence of reciprocal motivations for giving, as players give more to parents who have full information regarding the context in which giving occurs.